Handbook of IMF Facilities for Low-Income Countries. (Policy Papers; Policy Paper ;, 2012)
The Fund's concessional facilities are aimed at providing flexible and tailored support to low-income countries (LICs) in their efforts to achieve, maintain, or restore a stable and sustainable macroeconomic position consistent with strong and durable poverty reduction and growth.